HUBUNGAN ANTARA KLASIFIKASI STROKE DENGAN GANGGUAN FUNGSI KOGNITIF PADA PASIEN STROKE - Dewi Nopia; Zaqyyah Huzaifah (Journal of Nursing Invention, 2020)
Background: Stroke is the second leading cause of death in the world. Stroke is a vascular disorder caused by blockage or rupture of blood vessels in the brain, resulting in a clinical disorder due to damage to brain cells in certain parts. Symptoms can disrupt the process of mental activity or sublime cortilal function including cognitive function.Objective: This study aims to determine the relationship between stroke classification and impaired cognitive function in stroke patients.Methods: This study uses a correlation analysis method, with a cross-sectional design, a sample of 36 respondents according to the criteria, using Chi Square at α = 0.05. Results: There is a relationship between stroke classification and impaired cognitive function in stroke patients with a value of ρ value = 0.000.